Shrimp hepatopancreatic deoxyribonuclease — purification and characterization as well as comparison with bovine pancreatic deoxyribonuclease - Chou, Min-Yuan; Liao, Ta-Hsiu (Biochimica et biophysica acta, 1990)
Deoxyribonuclease (DNase), isolated from shrimp hepatopancreas by chromatography of DEAE-cellulose, Sephadex G-100, phenyl-Sepharose and hydroxyapatite, is homogeneous as shown by sodium dodecyl sulfate polyacrylamide gel electrophoresis. The metal ion requirements and the pH-activity optima of shrimp DNase are very similar to those of bovine DNase. Both shrimp and bovine DNases are sensitive to iodoacetate inactivation under the same condition. The active shrimp DNase molecule is a monoamer of M r 44 000, approx. 13 000 larger than the M r of bovine DNase. Shrimp DNase is rich in glutamic acid, glycine and half-cystine. The single polypeptide chani of shrimp DNase is highly cross-linked by 18 disulfides as compared to only two disulfides in bovine DNase. In contrast to bovine DNase, shrimp DNase is not a glycoprotein, is devoid of the activity against p-nitrophenyl phenylphosphonate (a synthetic substrate for bovine DNase), and resists to inactivation by β-mercaptoethanol or trypsin under the Ca 2+-free condition at pH 8. Shrimp DNase shows an isoelectric point of 4.06 on the thin-layer isoelectric focusing and rapidly loses its activity at pH below 5.